High-Resolution Approaches in Stratigraphic Paleontology - Harries, P. J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This volume delves into a spectrum of theoretical as well as applied aspects of high-resolution stratigraphic approaches in paleontology. It explores how increasingly detailed knowledge of the fossil record can enhance our understanding of the evolution of life on Earth and also allows geoscientists to address a broad range of important evolutionary and environmental questions in this arena. A 'zipped' version of the program CONOP9 2007 along with read-me files, sample files, and other documentation are available via a web site (see below). An earlier version of CONOP9 was initially supplied with 'High-Resolution Approaches in Stratigraphic Paleontology' (PJ Harries, editor) and described in Chapter 13 of that volume. This is an updated version of the program, and the documentation supplied with this version supersedes the information supplied in that chapter. To view the CONOP9 Programs, click on the link CONOP9 Programs on the right side of this page under Related links.
The Limits of Paleontological Resolution -- Best-Fit Intervals and Consensus Sequences -- Combining Stratigraphic Sections and Museum Collections to Increase Biostratigraphic Resolution -- Zoophycos, Systematic Stratigraphic Leaking, and Lamella Stratigraphy -- Variation in Adult Size of Scaphitid Ammonites from the Upper Cretaceous Pierre Shale and Fox Hills Formation -- Controls on Shell Shape in Acanthoceratid Ammonites from the Cenomanian-Turonian Western Interior Seaway -- A Reappraisal of the Relationship between Sea Level and Species Richness -- Diversity Patterns of Nonmarine Cretaceous Vertebrates of the Western Interior Basin -- Use of Event Beds and Sedimentary Cycles in High-Resolution Stratigraphic Correlation of Lithologically Repetitive Successions -- Late Devonian Sequence and Event Stratigraphy Across the Frasnian-Famennian (F-F) Boundary, Utah and Nevada -- Vertebrate Biostratigraphy of the Smoky Hill Chalk (Niobrara Formation) and the Sharon Springs Member (Pierre Shale) -- Limestone Concretions as Near-Isochronous Surfaces -- CONOP9 Programs for Solving the Stratigraphic Correlation and Seriation Problems as Constrained Optimization.
Keywords: Earth sciences; Paleontology; Sedimentology; Earth Sciences; Paleontology; Sedimentology; Earth Sciences, general; Electronic books